The effect of special exercises by a proposed training device to improve the angle of the body’s inclination for the two stages of starting and increasing speed and achievement ran 100 m under 18 years - Dawood, Abdul Alkaliq; Naji, Ahmed (Journal of Physical Education, 2019)
That many of the factors that play an important role in achieving the new achievement enemy (100) m, which requires interested, researchers and training personnel to study in order to identify mainly and enhance its role and importance in the achievement to be confirmed through training, and through the researcher and meet most Trainers for the field and field games, especially the jogging trainers, did not receive any special data for Iraqi athletes in the kinetic analysis to find out the real details on the running distance (100 m) and to identify the obvious weaknesses in the reaction stages, acceleration, maximum speed, Beware of the enemies of Iraq compared to the world champions in the effectiveness of (100) m, ranging from the tenths of the second, a very short but standard world achievement puts us in the back of the world, Asia and the Arabs. The researchers noticed that through his work as one of the trainers of athletics for the national team there is a problem at the beginning of the 100 meters, especially Milan body in the stages of the start and the stage of increasing speed that these stages are one of the most important stages of the 100 meters, which is determined by the race that the race 100 meters deals In the second parts, which makes the great importance be in the stages of departure and increasing speed. The aim of the study was to identify the effect of exercises prepared by a laser device to improve the angle of the body’s inclination during the start-up phase and the stage of increasing the speed of the 100-m active athlete. The researchers used the experimental method of the same group, and the study sample was determined by the intentional method that included the players of the specialized school of athletics. The training curriculum lasted for 6 weeks with 3 training modules using repetitive training method, On the raw results were processed statistically. The researchers concluded that exercises on the proposed device led to the development of starting angles and proved its efficiency and importance. The exercises on the device at different angles and their distances and heights have positively influenced the development of some physical characteristics accompanied by changes in biochemistry and development of achievement in the members of the research sample.